STRATEGI PEMASARAN EKSPOR PT GLOBAL TROPICAL SEAFOOD DALAM MENGHADAPI KOMPETISI PASAR GLOBAL - Malik, Jamaludin (Jurnal AGRISEP, 2015)
This research was aimed to identify the factors of strengths, weaknesses, opportunities, and threats in company's position for marketing strategy application, also to create the marketing strategy that applied in Global Tropical Seafood Co. (Ltd), Karawang. The analysis that use to evaluate the company's system are identified the internal factors combination (strengths and weaknesses), also external factors (opportunities and threats). All of the instruments in internal and external factors that identified, should be tested the validity and reliability. And to know the company's position for this time, SWOT analysis was used. Based on validity and reliability analysis's result, its explain that all of instruments in internal and external factors are valid and reliable to determine the export marketing strategy for fish handling crop of Global Tropical Seafood Co. (Ltd) on confident level at 95 %. SWOT's analysis result explain that for this time that the company is in first level (I quadrant), which is this position very beneficial to apply the strategy which support the growth oriented strategy. Based on the formula of SWOT's analysis strategy, so the SO's (Strengths and Opportunities) strategy that support the growth oriented strategy which is applied in Global Tropical Seafood Co. (Ltd) are raising biotechnology to increase production, developing and raising the marketing mix strategy, increasing the strength of sales team who is doing the market's expansion, increasing the relationship to cooperate with potential distributor in the export target countries, market's stimulate on fishery market which is very potential, also developing and expansion market area. Keywords: export marketing strategy, fish handling crop.